An Instrumental Measure of Hand and Facial Movement Abnormalities in Patients With Schizophrenia - Wang, Shu-Mei; Ouyang, Wen-Chen; Hsu, Hsiao-Man; Hsu, Li-Ta (Frontiers in Psychiatry, 2022)
Introduction: Movement disorders have been suggested to be a cardinal component of schizophrenia. With increased research interests in this area, instrumental measures are needed. This study was to examine if the motion capture system was reliable in measuring hand and facial bradykinesia and dyskinesia, and more sensitive to detecting movement differences between schizophrenia patients and healthy people than traditional rating scales. Methods: Sixteen schizophrenia patients and 20 healthy controls were recruited. Hand and facial bradykinesia and dyskinesia were measured using the motion capture system and rated using the Extrapyramidal Symptom Rating Scale and the Abnormal Involuntary Movement Scale. Results: The system showed strong test-retest reliability and generated larger effect sizes of group differences than did the rating scales. Conclusions: The results may support researchers and clinical practitioners to apply the system to sensitively measuring the hand and facial movement symptoms in schizophrenia patients, which contributes to gaining a deep understanding of movement issues in schizophrenia.